Antibiotic usage rates in bacterial versus nonbacterial diseases: a new way to monitor hospital-acquired infections in children: a retrospective case analysis - Gohil, Jayendra R.; Chaudary, Chintu C.; Sivanandan, Sheena D. (International Journal of Contemporary Pediatrics, 2020)
Background: While treating children, the selection of antibiotics, when indicated, should be from the point of its effectiveness, safety, suitability, and cost. However, this flow of action does not take place in all cases. Aim of the study was to assess the antibiotic usage in admitted children and mortality. Methods: The case records between January to July 2012 in children wards was evaluated for the use of antibiotics. Patients were grouped into; group A- ‘must use’ antibiotic in all, and group B- where antibiotics are not indicated. Results: There were 1852 admissions, including 719 Thalassemia cases. Antibiotic usage was 63% in 1133 cases after excluding thalassemia. Out of 1133 cases, 423 were in group A and 710 cases were in group B. In group B the antibiotic usage was 41%. The mortality was 6.6% and 4.8% in group A and B. Inside group B, mortality was 5.9% versus 4.0% in those administered versus not administered, antibiotics. Conclusions: There was no increase in mortality in patients in whom antibiotics were not prescribed, and no added benefit of prescribing antibiotics was observed in nonbacterial group B disease patients. The mortality was similar in both the groups. In nonbacterial group B, the antibiotics did not offer any advantage in the reduction of mortality, but increased the cost of the treatment, and possibly the chance of development of drug resistance and adverse events. When analysing the hospital antibiotic usage, only the nonbacterial diseases should be considered to get a true picture of the inappropriate prescription of antibiotics.